1997
DOI: 10.1007/bf02795771
|View full text |Cite
|
Sign up to set email alerts
|

Disorders of thyroid gland in India

Abstract: The profile of thyroid disorders encountered in pediatric and adolescent age groups in India is similar to that seen in most parts of the world except for the prevalence of iodine deficiency disorders in certain endemic regions of this country. Clinical presentation is most commonly for hypothyroidism and goiters and infrequently for hyperthyroidism. Of nearly 800 children referred for thyroid problems, 79% had hypothyroidism (goitrous as well as nongoitrous), 19% had euthyroid goiters and 2% had hyperthyroidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
60
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 10 publications
4
60
0
Order By: Relevance
“…Delayed diagnosis and treatment of hypothyroidism is common in India in spite of relatively high prevalence. [6] As progression of subclinical hypothyroidism to overt hypothyroidism occurs in a substantial number of subjects, [3] adequate thyroid supplementation in the presence of high serum TSH levels, antithyroid antibodies, enlarged thyroid gland and symptoms is justified.…”
Section: Discussionmentioning
confidence: 99%
“…Delayed diagnosis and treatment of hypothyroidism is common in India in spite of relatively high prevalence. [6] As progression of subclinical hypothyroidism to overt hypothyroidism occurs in a substantial number of subjects, [3] adequate thyroid supplementation in the presence of high serum TSH levels, antithyroid antibodies, enlarged thyroid gland and symptoms is justified.…”
Section: Discussionmentioning
confidence: 99%
“…[4,5] Regional and hospital based studies in India have shown a prevalence ranging from 9% to26%. [6] The prevalence is higher in lower socioeconomic groups. [6] Studies from neighboring countries like Nepal have also reported a higher incidence.…”
Section: Introductionmentioning
confidence: 99%
“…[6] The prevalence is higher in lower socioeconomic groups. [6] Studies from neighboring countries like Nepal have also reported a higher incidence. [7] Serum TSH levels are sensitive and specific for screening thyroid dysfunctions.…”
Section: Introductionmentioning
confidence: 99%
“…Deficiency of these hormones leads to irreparable damage to the growth and development, both physical as well as mental, of the child. 4,5 One of the main causes is congenital hypothyroidism, which is preventable. It is estimated to occur in 1 in 3000-4000 children in the world.…”
Section: Introductionmentioning
confidence: 99%
“…In India, this ratio is 1:2500. 4,5 Hypothyroidism ranges from an overt state of myxedema, end organ effects and multisystem failure to asymptomatic or subclinical condition with normal levels of thyroxine and triiodothyronine but mildly elevated levels of thyrotropin. [6][7][8][9] The prevalence of hypothyroid in the developed world is estimated to be about 4-5% while subclinical hypothyroidism is estimated to be about 4-15%.…”
Section: Introductionmentioning
confidence: 99%